Smoking cessation induces rapid healing in elderly patient with traumatic ulcerative granuloma with stromal eosinophilia (TUGSE): a rare case report - Febryna, Chivita Wulandari; Nur’aeny, Nanan (Universitas Padjadjaran, 2025)
Introduction: Traumatic Ulcerative Granuloma with Stromal Eosinophilia (TUGSE) is a type of chronic traumatic ulcer. There are several factors that contribute to the development of TUGSE, but trauma is the primary one. If smoking or other risk factors are present, the condition may be exacerbated, as this may impede the healing of wounds. This case report will show the influence of smoking cessation on the recovery from TUGSE in patients and the resulting improvement in quality of life. Case report: A 64-year-old male patient presented to the dental hospital with a primary complaint of a painful sore on the tip of his tongue at the back for the past month. The patient had previously consulted a general practitioner and an ear, nose, and throat (ENT) specialist and was prescribed triamcinolone acetonide and povidone iodine mouthwash but no improvement was observed. An intraoral examination revealed an ulcer on the lateral side of the tongue. The patient had a cavity with sharp edges near the lesion, but it was ground down 2 days ago. The patient had a history of smoking clove cigarettes, consuming 24 sticks per day for more than five years. The patient was given chlorhexidine gluconate 0.2% mouthwash, to be used at a dose of 10ml, twice a day, and was instructed to apply a thin layer of triamcinolone acetonide 0.1% in orabase three times a day on the lesion. The patient recovered after seven days of treatment and reported their symptoms have decreased. The assessment using the Oral Health Impact Profile-14 (OHIP-14) indicated an improvement in the patient quality of life. Conclusion: Smoking cessation can improve the healing process of ulcers, thereby improving an individual's quality of life.